2016
DOI: 10.1128/aac.00539-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of gyrB Mutations in Pre-extensively and Extensively Drug-Resistant Tuberculosis in Thai Clinical Isolates

Abstract: DNA gyrase mutations are a major cause of quinolone resistance in Mycobacterium tuberculosis. We therefore conducted the first comprehensive study to determine the diversity of gyrase mutations in pre-extensively drug-resistant (pre-XDR) (n ‫؍‬ 71) and extensively drug-resistant (XDR) (n ‫؍‬ 30) Thai clinical tuberculosis (TB) isolates. All pre-XDR-TB and XDR-TB isolates carried at least one mutation within the quinolone resistance-determining region of GyrA ( . MIC and DNA gyrase supercoiling inhibition assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
2
23
1
2
Order By: Relevance
“…Confirmation of these lower critical concentrations have come from clinical studies [209][210][211][212][213] and several investigations [214][215][216][217][218][219][220][221] of drug resistance-associated mutations in isolates with MICs below the standard breakpoint. Clinical studies using assumption-free methods such as machine learning have confirmed that these values (table 3) are in fact the MICs above which tuberculosis patients fail combination therapy.…”
Section: Rv1910cmentioning
confidence: 91%
See 1 more Smart Citation
“…Confirmation of these lower critical concentrations have come from clinical studies [209][210][211][212][213] and several investigations [214][215][216][217][218][219][220][221] of drug resistance-associated mutations in isolates with MICs below the standard breakpoint. Clinical studies using assumption-free methods such as machine learning have confirmed that these values (table 3) are in fact the MICs above which tuberculosis patients fail combination therapy.…”
Section: Rv1910cmentioning
confidence: 91%
“…Additionally, studies have been done in which treatment failed in patients who were infected with M tuberculosis who had drug target site mutations, but MICs were lower than current breakpoints, and were more consistent with the newly proposed breakpoints. [214][215][216][217][218][219][220][221] Therefore, the proposed concentrations have higher sensitivity for clinical decision making, and should be used to estimate the global burden of MDR tuberculosis.…”
Section: Rv1910cmentioning
confidence: 99%
“…Two studies in South Africa 92,97 found that mutations at common codons 90 and 94 resulted in increases in MIC up to 2.00 mg/L, and studies in China and Thailand with similar findings also reported much higher MICs of up to 16.00 mg/L in a small percentage of patients with these and other mutations. 98,99 A recent survey conducted in South Africa, Eastern Europe, and Asia found that resistance was between 0.9% and 14.6% for moxifloxacin when tested at 0.50 mg/L and much lower in all countries when tested at 2.00 mg/L. 94 The study also determined resistance to moxifloxacin among patients with rifampicin-sensitive and rifampicinresistant isolates.…”
Section: Drug Resistancementioning
confidence: 99%
“…In contrast, mutations in the QRDR of gyrB, although found much less frequently (Յ2%) than the gyrA mutations, showed different MIC levels among the quinolones. The GyrB Glu540Asp mutation has been shown to mediate higher MICs of later quinolones, particularly 8-methoxy quinolones like MOFX, than of early quinolones (12). In this study, the gyrA and gyrB genes of 53 OFX-resistant strains were sequenced.…”
Section: Discussionmentioning
confidence: 99%